Research on networking troubleshooting method based on software defined network - Jia-wei LI; Zhi-ju YANG; Xi-jun LIN; UHai-peng Q (网络与信息安全学报)
Based on the reaserch status of networking troubleshooting in software defined network,a new net-working troubleshooting method was proposed.A TCP packet marked in head field was sent and detailed forward information in every hop would be written in its data filed once the test packet was matched.Taking advantages of the programmable feature of the controller and OpenFlow extensible match,special flow table was designed for matching test-used packet.The analysis module extracted and split the forward information,and thus printed the suspicious network problem which can be used to track and located the problematic network node.The experiment results indicate that the proposed method is fairy efficient.